Project benefits management in IT projects - An Australian perspective - Bennington, Peter; Baccarini, David (2004)
Information technology (IT) projects are implemented in organizations to provide benefits. This paper reports the research findings into the process of benefits management by project managers in IT projects in Perth, Western Australia. It was found that IT project managers have a strong propensity towards efficiency benefits rather than effectiveness benefits. A significant majority of IT project managers do not assign Key Performance Indicators (KPIs) to project benefits, which makes it difficult to assess if benefits have been delivered. Project managers tend to focus on managing deliverables rather than the benefits that should result from utilization of the deliverables. Many of the findings indicate that there is significant room for improvement in the formal effective application of project benefits management. - Reproduced.
Keywords: Information technology; Project management